A catered murder - Crawford, Isis (Crawford, Isis. Mystery with recipes., 2003)
When Bernadette Simmons goes to work for her sister Libby's catering business in New York, it's a recipe for disaster as the two find themselves in the midst of a murder mystery they can really sink their teeth into. It's only been a few days since Bernie and Libby started working together at A Little Taste of Heaven, and already they've got their hands full - baking cookies and slicing rare beef tenderloin to serve at a high school reunion. The dinner has a "Dracula" theme and a very strange guest of honour: Laird Wrenn, a New York Times bestselling author of vampire novels. Libby and Bernie know this will be an evening unlike any other. And they're proven right when Laird pours a glass of water, takes a long sip - and drops stone-cold dead...Now, with murder on the menu and Libby under suspicion, the sisters will have to put their heads together to figure out whodunit - in a mystery that promises to be deadly to the very last bite.